Случайные колебания рам тележек вагонов метрополитена с учетом неровности пути - Белоцерковский, Александр Борисович; Жовдак, В. А.; Черных, О. В.; Ярошок, Ю. А. (НТУ "ХПИ", 2003)
The problem of definition of probability performances of the bogie frames of transit vehicles at random action is considered. The random action is caused by track irregularities. The external load is modelled by the stationary random process. The calculation is executed by the finite element method and the method of spectral representations. The program system COSMOS/M was used. The mode deformation of the system was investigated at the different models of the loading
Keywords: дисперсия возмущения; спектральная плотность; случайные колебания; вынужденные колебания; дисперсия перемещения